Paper/Carbon Nanotube-Based Wearable Pressure Sensor for Physiological Signal Acquisition and Soft Robotic Skin - Zhan, Zhaoyao (2017)
A wearable and flexible pressure sensor is essential to the realization of personalized medicine through continuously monitoring an individual’s state of health and also the development of a highly intelligent robot. A flexible, wearable pressure sensor is fabricated based on novel single-wall carbon nanotube /tissue paper through a low-cost and scalable approach. The flexible, wearable sensor showed superior performance with concurrence of several merits, including high sensitivity for a broad pressure range and an ultralow energy consumption level of 10–6 W. Benefited from the excellent performance and the ultraconformal contact of the sensor with an uneven surface, vital human physiological signals (such as radial arterial pulse and muscle activity at various positions) can be monitored in real time and in situ. In addition, the pressure sensors could also be integrated onto robots as the artificial skin that could sense the force/pressure and also the distribution of force/pressure on the artificial skin.